2006
DOI: 10.1128/aac.00503-06
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Outpatient Fecal Colonization Due to Escherichia coli Isolates with Decreased Susceptibility to Fluoroquinolones: Longitudinal Study of Patients Recently Discharged from the Hospital

Abstract: Among 10 subjects colonized with Escherichia coli isolates with reduced susceptibility to fluoroquinolones, the median duration of colonization following hospital discharge was 80 days (range, 8 to 172 days). Colonization was longer for isolates demonstrating organic-solvent tolerance than for isolates that were not organicsolvent tolerant (151 versus 29 days, respectively; P ‫؍‬ 0.07) but was not associated with other resistance mechanisms, demographics, or antibiotic use.Significant increases in the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…This carriage rate is in line with recently reported rates of carriage of selected gram-negative bacteria among newly hospitalized patients (7%) [3], healthy vegetarians (14%) [3], and Saudi Arabian inpatients (26%) [4]. The persistence of these strains is also not unexpected, given published evidence regarding long-term persistence of strains of Escherichia coli [5][6][7]. The authors do not discuss the 80% of subjects who were not carrying MDRGNB, but one might surmise that the majority of them were colonized with other gram-negative bacteria, as are most humans, and that the natural history of their colonization might be similar.…”
supporting
confidence: 88%
“…This carriage rate is in line with recently reported rates of carriage of selected gram-negative bacteria among newly hospitalized patients (7%) [3], healthy vegetarians (14%) [3], and Saudi Arabian inpatients (26%) [4]. The persistence of these strains is also not unexpected, given published evidence regarding long-term persistence of strains of Escherichia coli [5][6][7]. The authors do not discuss the 80% of subjects who were not carrying MDRGNB, but one might surmise that the majority of them were colonized with other gram-negative bacteria, as are most humans, and that the natural history of their colonization might be similar.…”
supporting
confidence: 88%
“…They showed that, among a cohort of 10 colonized outpatients, the median duration of colonization was 80 days (range, 8-172 days). They further showed that prolonged colonization was more common among species that overexpressed the AcrAB efflux pump [19]. Future studies will need to determine whether certain antimicrobial resistance characteristics among P. mirabilis also promote persistent colonization.…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, among the 15 multidrug-resistant P. mirabilis isolates, 13 represented genetically unrelated strains, and therefore, acquisition of a potential outbreak strain would not explain persistent colonization. Lautenbach et al [19] analyzed potential factors associated with persistent colonization among E. coli strains with reduced susceptibility to fluoroquinolones. They showed that, among a cohort of 10 colonized outpatients, the median duration of colonization was 80 days (range, 8-172 days).…”
Section: Discussionmentioning
confidence: 99%
“…: transient versus chronic carriage) is still poorly known and the cross-sectional design of our survey did not address the dynamics of ESBLE carriage [38]. Data from prior studies have suggested that gut colonization could change over time and that it may be markedly influenced through antibiotic selection pressure [39].…”
Section: Discussionmentioning
confidence: 99%